STUDY OF GONADOTOXIC ACTION OF ETHYL ESTER Α- BROMISOVALERIAN ACID - Turkina, V.A. (World of Medicine and Biology, 2016)
The purpose of conducted studies was to find out changes in organometric parameters of testicles and functional values of spermatozoa in adult rats which received 32.8 mg / kg and 6.56 mg / kg of ethyl α-bromo-isovalerate directly to stomach. The only changes to be observed was a significant increase of relative weight of the testicles. Such an effect could be considered as an eventual gonadotoxicity of the compound. Received data can be used in further studies in order to better understand the changes of morphological values of seminiferous epithelium in rats.
Keywords: gonadotoxic effect; ethyl ester of α-bromoisovaleric acid; laboratory rats